2023
DOI: 10.1080/19490976.2023.2195792
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics for biomarker approaches in the diagnostic evaluation and management of abdominal pain and irritable bowel syndrome: what lies ahead

Abstract: Reliable biomarkers for common disorders of gut–brain interaction characterized by abdominal pain, including irritable bowel syndrome (IBS), are critically needed to enhance care and develop individualized therapies. The dynamic and heterogeneous nature of the pathophysiological mechanisms that underlie visceral hypersensitivity have challenged successful biomarker development. Consequently, effective therapies for pain in IBS are lacking. However, recent advances in modern omics technologies offer new opportu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 164 publications
0
2
0
Order By: Relevance
“…Temporary changes in the composition of the GI microbiota during a critical developmental period have long-term effects on nociceptive pathways, and the gut microbiome in particular in male newborns but not adult rats (O'Mahony et al, 2014). Histamine is emerging as a relevant mediator of visceral hyperalgesia (De Palma et al, 2022), and multiple studies investigating the highly complex processes are well summarised in several recent review articles (Alizadeh et al, 2022;Ustianowska et al, 2022;Mayer et al, 2023;Pujo et al, 2023;Sarnoff et al, 2023;Shaikh et al, 2023;Shin and Kashyap, 2023). 9 Sex-specific differences…”
Section: Gut Microbiome and Pain Disordersmentioning
confidence: 99%
“…Temporary changes in the composition of the GI microbiota during a critical developmental period have long-term effects on nociceptive pathways, and the gut microbiome in particular in male newborns but not adult rats (O'Mahony et al, 2014). Histamine is emerging as a relevant mediator of visceral hyperalgesia (De Palma et al, 2022), and multiple studies investigating the highly complex processes are well summarised in several recent review articles (Alizadeh et al, 2022;Ustianowska et al, 2022;Mayer et al, 2023;Pujo et al, 2023;Sarnoff et al, 2023;Shaikh et al, 2023;Shin and Kashyap, 2023). 9 Sex-specific differences…”
Section: Gut Microbiome and Pain Disordersmentioning
confidence: 99%
“…3 ). For instance, within IBS models, bioengineering offers the exploration of genetic and epigenetic influences through whole genomic sequencing [ 182 , 183 ], as well as transcriptomics for identifying biomarkers [ 184 ]. Epigenomic mechanisms influenced by intricate environmental factors may affect the genome, leading to potential implications for IBS [ 183 ].…”
Section: Future Directions and Challenges For Bioengineering Within Gwimentioning
confidence: 99%
“…Interestingly, their results showed that the visceral hypersensitivity phenotype could be transferred to animal models through fecal transfer and rescued by fungicide treatment. 10 Shin et al 11 point at a gap in clinical translation, where reliable biomarkers for common disorders of gut – brain interaction characterized by abdominal pain, including but not limited to IBS, are needed to develop individualized therapies.…”
mentioning
confidence: 99%